Prebiotic and Synbiotic Effects of Lactobacillus rhamnosus Isolated from Iraq on Intestinal Tract Microflora in Mice - Mohammed, Sarmad Ghazi; Sahi, Ali Ahmed; Ameer, Nawfal Abdul; Fusheng, Chen (Pakistan Journal of Nutrition, 2011)
In this study, Kunming mice were fed with galactooligosaccharide and Lactobacillus rhamnosus which isolated in former study from breast fed healthy infants feces in Basrah province, Iraq and chose as potential probiotic. The feed conversion efficiency and body weight of mice, contents of water and short chain fatty acid of mice feces and intestinal tract microflora in mice, were systematically investigated. The results revealed that the best treatment was when the mice (group f) were fed with infant formula plus galactooligosaccharide and L. rhamnosus, that gave best feed conversion efficiency (36.49), an increasing in Lactobacilli (9.45 cfu) and Bifidobacterium (7.35 cfu) counts and decreasing in Staphylococci (4.44 cfu) and Coliform (5.46 cfu) counts in mice feces, decreasing fecal pH (5.92), increasing fecal water content (69.71%) and best increasing in fecal SCFAs concentration of formic (1.066 μmol/g), acetic (24.766 μmol/g), propionic (16.644 μmol/g) and butyric (4.842 μmol/g) after 6 weeks of assay comparing with other groups.